Transformasi Digital dalam Sektor Keuangan: Peluang dan Risiko bagi UMKM di Desa Tertinggal (3T) - Huda, Syamsul; Yuliati, Anik (Jurnal Locus Penelitian dan Pengabdian, 2025)
Digital transformation is very important for MSMEs in villages because it opens up opportunities to expand markets and expand access to hard-to-reach resources, thereby driving economic growth. However, MSMEs in underdeveloped villages (3T) are not all digitally literate. This study aims to look at the opportunities and risks faced by MSMEs in disadvantaged villages (3T) and how to adapt to digital transformation in the financial sector. This research uses a qualitative approach with a literature study method from the latest scientific articles of the last 10 years and credible books to see the opportunities and risks faced by MSMEs in disadvantaged villages (3T) and how to adapt to digital transformation in the financial sector. The results show that digital transformation, with e-commerce and social media, opens up great opportunities for MSMEs in disadvantaged villages (3T) to reach a wider market, work more efficiently, and obtain capital more easily. However, there are also big challenges such as lack of digital knowledge, uneven internet, complicated regulations, and fear of new technology. Limited capital is also a problem, especially for MSMEs in underdeveloped villages (3T). The adaptation that must be done by MSMEs in disadvantaged villages (3T) is digital literacy. The hope of this research is to produce a comprehensive understanding of the opportunities that can be seized and the risks that must be overcome by MSMEs in disadvantaged villages (3T) due to the digital transformation of the financial sector, so that appropriate strategies can be formulated to support the sustainable development of MSMEs.